2007
DOI: 10.1103/physrevb.76.205110
|View full text |Cite
|
Sign up to set email alerts
|

VO: A strongly correlated metal close to a Mott-Hubbard transition

Abstract: Here, we present experimental and computational evidences to support that rocksalt cubic VO is a strongly correlated metal with non-Fermi-liquid thermodynamics and an unusually strong spin-lattice coupling. An unexpected change of sign of metallic thermopower with composition is tentatively ascribed to the presence of a pseudogap in the density of states. These properties are discussed as signatures of the proximity to a magnetic quantum phase transition. The results are summarized in an electronic phase diagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Therefore, the scaling exponent of the powerlaw term of the resistivity as a function of temperature (n) is often used to infer the type of interactions ruling the metal state. In materials with strong electron-electron interactions and undergoing ordering phenomena, other exponents (n ≠ 1, 2) are usually observed, being the physics behind this so-called 'Non-Fermi liquid' (NFL) behaviour [11][12][13] , a subject of active discussion [14][15][16][17] .…”
mentioning
confidence: 99%
“…Therefore, the scaling exponent of the powerlaw term of the resistivity as a function of temperature (n) is often used to infer the type of interactions ruling the metal state. In materials with strong electron-electron interactions and undergoing ordering phenomena, other exponents (n ≠ 1, 2) are usually observed, being the physics behind this so-called 'Non-Fermi liquid' (NFL) behaviour [11][12][13] , a subject of active discussion [14][15][16][17] .…”
mentioning
confidence: 99%
“…The band is ascribed to the partially filled conduction band mostly composed of V 3d components. Theoretical studies have predicted that the V 3d band in the occupied region is mostly composed of the t 2g states [20,21]. It is deduced from the results of resonant PES measurements that the valence band of the VO film mostly composed of O 2p components appears at 4-10 eV overlapping with the substrate Ag 4d band that is attenuated by the inelastic scattering of Ag 4d photoelectrons in the VO overlayer, as will be discussed later.…”
Section: Resultsmentioning
confidence: 92%
“…The electronic structures of 3d transition metal monoxides have attracted attention because these are promising candidates for the model systems to understand the properties of highly correlated electron systems owing to their structural and electronic simplicity. It has been revealed that the monoxides of Mn, Fe, Co, and Ni (group 7, 8, 9, and 10 transition metals, respectively) are antiferromagnetic insulators while TiO (group 4 transition metal monoxide) is a Fermi-liquid metal [21]. VO (group 5 transition metal monoxide) locates in the midst of these two groups, and the electronic structure has attracted attention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the errors of vanadium oxides are relatively large because they fitted the energy adjustment of V element with all binary vanadium oxides. VO is a strongly correlated metal exhibiting different character compared with other vanadium oxide semiconductors. Thus, we modify the energy adjustment of V element to be 1.564 eV without considering VO.…”
Section: Resultsmentioning
confidence: 99%